The importance of sex as a risk factor for hospital readmissions due to pulmonary diseases - Alessandra Buja; Anna De Polo; Elisa De Battisti; Milena Sperotto; Tatjana Baldovin; Silvia Cocchio; Patrizia Furlan; Mario Saia; Maria Luisa Scapellato; Guido Viel; Vincenzo Baldo; Chiara Bertoncello; et al. (BMC, 2020)
Abstract Background Pulmonary diseases are a common and costly cause of 30-day readmissions. Few studies have focused on the difference in risk for rehospitalization between men and women in older patients. In this study we analyzed the association between sex and the risk of readmission in a cohort of patients admitted to the hospital for chronic obstructive pulmonary disease (COPD) exacerbation and other major pulmonary diseases. Methods This was a retrospective cohort study based on administrative data collected in the Veneto Region in 2016. We included 14,869 hospital admissions among residents aged ≥65 years for diagnosis related groups (DRGs) of the most common disorders of the respiratory system: bronchitis and asthma, pneumonia, pulmonary edema, respiratory failure, and COPD. Multilevel logistic regressions were performed to test the association between 30-day hospital readmission and sex, adjusting for confounding factors. Results For bronchitis and asthma, male patients had significantly higher odds of 30-day readmission than female patients (adjusted odds ratio (aOR), 2.07; 95% confidence interval (CI), 1.11-3.87). The odds of readmission for men were also significantly higher for pneumonia (aOR, 1.40; 95% CI, 1.13-1.72), for pulmonary edema and respiratory failure (aOR, 1.28; 95% CI, 1.05-1.55), and for COPD (aOR, 1.34; 95% CI, 1.00-1.81). Conclusions This study found that male sex is a major risk factors for readmission in patients aged more than 65 years with a primary pulmonary diagnosis. More studies are needed to understand the underlying determinants of this phenomena and to provide targets for future interventions.